Prison health care in South Africa: a study of prison conditions, health care and medical accountability for the care of prisoners - Van Heerden, Judith (Department of Medicine, 2016)
This quantitative and qualitative study investigates the type and quality of health care and conditions of imprisonment that prevailed in some South African prisons in the late 1980s. It was inspired by political activists who were incarcerated, yet despite, or because of, the harsh conditions in prison persisted with their struggle for human rights. Appeals for the improvement of prison conditions which they submitted to the authorities are unique primary source documents. By implication, this survey adds value to their cause, for several issues examined in it had already been raised while they were in prison. With most information on prisons restricted until 1992, there was no body of literature on South African prison health care to review. Instead, Chapter 1 outlines the historical background of imprisonment in South Africa and key penal legislation. It also deals with events like the Biko affair which, in the recent past, affected the medical profession, the response of professional organisations to these events, and the national and international repercussions. Chapter 2 on the methodology describes the study design, data collection process and the limitations of the survey. Numerous attempts to interview District Surgeons and visit prisons were fruitless, consequently reducing the intended scope of the primary research. Because these external limitations affected the study design, they are discussed under methodology. A semi-structured questionnaire was developed to collect information about health care while imprisoned during the States of Emergency ( 1986-1990). Interviews based on this questionnaire were conducted with 123 ex-detainees from the Eastern and Western Cape. The results of the study are presented in Chapter 3, both quantitative, in the breakdowns of the data relating to each of the 14 questions, and qualitative, in the tables which reflect individual experiences and comments. The significance of these results is examined in the discussion in Chapter 4, backed by other supportive evidence. It begins by sketching general conditions of imprisonment, using unsolicited information from the interviewees, and proceeds to discuss health care services as they pertained during the study period. Many points of discussion also draw on the seven Case Reports and the report on North End Prison, Port Elizabeth, which have been added as an appendix to that chapter. The research indicates a disregard for the well-being of and failure to provide adequate health care for individuals at the mercy of detaining authorities. This situation was compounded by collusion among the forces of law and order and District Surgeons, and a scant response by academics and professional organisations to problems associated with imprisonment, isolation and torture. In the conclusion, Chapter 5, strategies for improving prison health care are explored. They are based on current national and international literature, policy and practice. The main proposals for reform are then summarised in the recommendations in Chapter 6. These range from revising legislation so as to accord with the constitutional rights of prisoners to addressing the training and attitudes of personnel, establishing health care standards and auditing mechanisms, and creating a more open prison system.